OC-018 Audit of Helicobacter Pylori Testing in Microbiology Laboratories in England: In Line with Nice Guidance? Is There Scope for Routine Surveillance of Antibiotic Resistance?. (17th August 2016) - Allison, R; Lecky, DM; Bull, M; Turner, K; Godbole, G; McNulty, CA
Abstract : Introduction: Current guidance from the National Institute for Health and Clinical Excellence (NICE) recommends that clinicians test for Helicobacter pylori using a carbon-13 urea breath test or a stool antigen test, or laboratory-based serology where its performance has been locally validated. Recommended first-line treatment suggests a proton pump inhibitor (PPI) with dual antibiotic therapy. Aims: To assess: microbiology laboratory compliance with NICE guidance; and to determine the number of laboratories performing culture and antibiotic susceptibility testing which will inform decisions on future national H. pylori antibiotic resistance surveillance strategies. Methods: In 2015, questionnaires were sent by e-mail to 170 Clinical Pathology Accreditation (CPA) labs in England. All non-responding labs were contacted and requested to complete the questionnaire by e-mail or telephone. Results: Of the 121/170 (71%) labs that responded, 96% provide a H. pylori testing service: 78% perform on site and 13% refer elsewhere. In line with NICE guidance: 95% of labs comply by testing with stool antigen or urea breath test for H. pylori . Five labs do not comply as they perform serology or biopsy urease tests first line (4/5 encourage urea breath tests in their acute trusts). Cultures and antibiotic susceptibility performed: 23% of labs perform H. pylori cultures on site; 46% refer biopsy specimens to another lab (39/43 (91%) refer to the Helicobacter Reference Unit (HRU)). Of the 22 labs undertaking H. pylori cultures; two processed ten specimens/week; others ≤1 specimen/week. Nine labs undertake antibiotic susceptibility on site; nine refer elsewhere (8/9 to the HRU). Eight of nine labs that reported testing for antibiotic susceptibility in-house commented on the antibiotics tested: metronidazole-7/8 labs (88%); clarithromycin-6/8 labs (75%); amoxicillin-7/8 labs (88%); tetracycline-5/8 labs (63%); levofloxacin-2/8 labs (25%). Conclusion: The majority of labs are complying with NICE guidance. However, the four labs still performing serology and one performing biopsy urease tests as their first line diagnostic test for H. pylori should be followed up and have the current guidance reinforced. As very few laboratories are routinely performing culture of biopsy specimens to investigate antibiotic susceptibility, an English culture based surveillance system would probably need centralised culture. However, a PCR based stool specimen surveillance system would be very possible, but thus far, does not give metronidazole susceptibility. Disclosure of Interest: R. Allison: None Declared, D. Lecky: None Declared, M. Bull: None Declared, K. Turner: None Declared, G. Godbole: None Declared, C. McNulty Consultant for: PHE diagnostic guidance for H. pylori and PHE antibiotic guidance